Juvenile justice a reference handbook - Shoemaker, Donald J.; Wolfe, Timothy W. (Santa Barbara, California ABC-CLIO, an imprint of ABC-CLIO, LLC, 2016)
"Authoritative, current, and easy to use, this book is an outstanding resource for readers looking to gain an accurate and thorough understanding of American juvenile justice. Presents historical and contemporary data in an easy-to-understand fashion that survey the complex history of the juvenile justice system and allow readers to better comprehend the key issues Includes a perspectives chapter that enables readers to hear voices from individuals with different backgrounds who are concerned with juvenile justice Provides an ideal resource for general readers who want to learn more about the history and current events concerning juvenile justice as well as students without previous background knowledge of the subject Contains a chronology of key moments in the history of juvenile justice in the United States as well as a glossary of key terms and definitions to guide the reader"-- Provided by publisher.
"Juvenile delinquency is a topic that has interested the public and academic scholars for decades. When hearing the word "delinquent," most people think of street gangs or bands of teens running loose and frightening people in streets or parks. However, delinquency covers a range of behaviors from minor offenses, such as trespassing, to the more serious crimes often associated with gangs"-- Provided by publisher.
Revised edition of the authors' Juvenile justice, 2005.
Dr. Phoebe Zoe Maria U. Sanchez (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Juvenile justice, Administration of -- United States -- Handbooks, manuals, etc; LAW / Child Advocacy; LAW / Criminal Law / Juvenile Offenders